(untitled) (translation. a transdisciplinary journal, 2022)
The present paper attempts to read certain episodes in nineteenth century colonial Calcutta as processes of cultural translation. The translational aspect of the colonial encounter has been largely unnoticed. The cul rural traffic, the movement of languages, books, genres and ideas indicate a larger process of cultural translation at work. In rethinking how cultures relate to one another at moments of cultural encounter, I have tried co emphasize the crucial role chat genres play in such a process. Through a select reading of the novel and some popular prinr genres in nineteenth cenrury Calcurt.a I suggest that instead of a stable mimetic theory of art we need to approach the colonial encounter as a process of constant negotiation and exchange, of translational departures which in rum helps us unsercle conventional notions of the rigidity of genre boundaries enabling a furthering of processes of translation.